2015
DOI: 10.1186/s13069-015-0026-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for clinical use of reprogrammed cells for autologous treatment of macular degeneration

Abstract: Since the discovery of induced pluripotent stem cells (iPSC) in 2006, the symptoms of many human diseases have been reversed in animal models with iPSC therapy, setting the stage for future clinical development. From the animal data it is clear that iPSC are rapidly becoming the lead cell type for cell replacement therapy and for the newly developing field of iPSC-derived body organ transplantation. The first human pathology that might be treated in the near future with iPSC is age-related macular degeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 87 publications
(96 reference statements)
0
11
0
Order By: Relevance
“…Induced pluripotent stem cells (iPSCs) are a valuable source for generating retinal pigment epithelium (RPE) for transplantation to alleviate visual impairment associated with age‐related macular degeneration, a disease that afflicts 20 to 25 million people worldwide [1, 2]. On the basis of pioneering work done with in vitro RPE differentiation and with surgical techniques to transplant RPE monolayers in the eye [36], pluripotent stem cell‐derived RPE is considered an ideal target for the development and optimization of stem cell therapy. However, generating stem cell‐based therapy requires well‐defined and authenticated iPSC‐RPE [7].…”
Section: Introductionmentioning
confidence: 99%
“…Induced pluripotent stem cells (iPSCs) are a valuable source for generating retinal pigment epithelium (RPE) for transplantation to alleviate visual impairment associated with age‐related macular degeneration, a disease that afflicts 20 to 25 million people worldwide [1, 2]. On the basis of pioneering work done with in vitro RPE differentiation and with surgical techniques to transplant RPE monolayers in the eye [36], pluripotent stem cell‐derived RPE is considered an ideal target for the development and optimization of stem cell therapy. However, generating stem cell‐based therapy requires well‐defined and authenticated iPSC‐RPE [7].…”
Section: Introductionmentioning
confidence: 99%
“…The hematopoietic stem cells have already been used in clinic to treat disease such as multiple myeloma and leukemia [ 54 ]. Recently, Japanese scientists applied human iPSCs in curing ophthalmological diseases in real patients [ 55 ]. It has also been well envisioned that in the near future we can have human iPSC derived organs for transplantation surgery [ 56 ].…”
Section: Cell Replacement Strategies and Challengesmentioning
confidence: 99%
“…A mature transplantation protocol for PD treatment should not only address the safety issues discussed above but also refine an optimal differentiation protocol to ensure proper cell identities and long-term functions [ 98 100 ]. Hopefully, lessons and progress learned from clinical trials using iPSC products in other diseases can lend some useful experience [ 55 , 86 ].…”
Section: Cell Replacement Strategies and Challengesmentioning
confidence: 99%
“…A recent review identified that many aspects of the adaptive and innate immune system mechanisms are yet to be explored in detail for human cells . Data from human transplanted autologous reprogramed cells in vivo is limited and only one current clinical trial for iPSC‐RPE cells exists that found edema in the patient retina most likely from the surgical intervention for the transplanted iPSC‐RPE cell sheet . As the field grows and moves closer to clinical application the need to understand the extent of the immune response to transplanted human iPSC‐derived cells becomes paramount.…”
Section: Introductionmentioning
confidence: 99%